SANKSI PIDANA TERHADAP PERANTARA PERDAGANGAN NARKOTIKA - HOTMAIDA SIMANJUNTAK (LP2MTBM MAKARIOZ, 2019)
Drug crime is a special crime. As with specific criminal offenses, judges are allowed to punish two main crimes at once, in general corporal sentences and criminal fines. Corporal punishment in the form of capital punishment, life imprisonment, or imprisonment. The goal is that the punishment will burden the perpetrators so that crime can be overcome in the community, because drug crimes are very dangerous to the interests of the nation and state.The problem in this study is how the legal regulation of Narcotics trafficking, How the Narcotics Trafficking Criminal Liability Accountability, How Judgment and Judgment in Case No. 278 / Pid.Sus / 2015 / PN.Bnj. The research method used is the Empirical Juridical approach and is Normative Empirical.The results showed that narcotics illicit trafficking is an extra ordinary crime because it is a transnational crime regulated in a special law, namely Law No. 35/2009 concerning Narcotics. Narcotics traffickers can be held criminally liable as regulated by law in Articles 114, 119, 124, 129 of Law Number 35 Year 2009 concerning Narcotics. With the threat of Death Penalty, Criminal Prison and Criminal Penalty. Judge's Consideration in Case No. 278 / Pid.Sus / 2015 / PN.Bnj is proven and the fulfillment of criminal elements charged by the public prosecutor which is corroborated by the evidence presented and the legal facts revealed in the trial.